(untitled) (CIPEEX, 2025)
Aquaponics is a method of growing food that involves the integration of aquaculture and hydroponics in water and nutrient recirculation systems. It presents itself as a real alternative for food production with less impact on the environment, due to its sustainability characteristics. The objective of this study was to develop and implement a fish farming project for tilapia and tambacu in a reservoir of up to 1,000 liters to evaluate fish growth. The project was carried out in the outdoor area of the UniEVANGÉLICA Veterinary Clinic, located in the urban center of Anápolis. The fish farming systems were set up and adapted to include the following components: fish pond, biological filter, and water pump. After 100 days of monitoring, the weight gain of the tilapia was 10 times greater than that of the tambacu. It is possible that the climate of Anápolis is not favorable for the cultivation of tambacu in a domestic fish farming system.